Touch-display keyboards: transforming keyboards into interactive surfaces - Villar, Nicolas (Proceedings of the 28th international conference on Human factors in computing systems, 2010)
In spite of many advances in GUI workstations, the keyboard has remained limited to text entry and basic command invocation. In this work, we introduce the Touch-Display Keyboard (TDK), a novel keyboard that combines the physical-ergonomic qualities of the conventional keyboard with dynamic display and touch-sensing embedded in each key. The TDK effectively transforms the keyboard into an interactive surface that is seamlessly integrated with the interaction space of GUIs, extending graphical output, mouse interaction and three-state input to the keyboard. This gives rise to an entirely new design space of interaction across keyboard, mouse and screen, for which we provide a first systematic analysis in this paper. We illustrate the emerging design opportunities with a host of novel interaction concepts and techniques, and show how these contribute to expressiveness of GUIs, exploration and learning of keyboard interfaces, and interface customization across graphics display and physical keyboard.